2020
DOI: 10.4274/jtgga.galenos.2019.2019.0059
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic importance of atypical glandular cells in cervico-vaginal cytology

Abstract: Objective: To analyze the histopathologic outcomes of patients with atypical glandular cells (AGC) in cervicovaginal cytology examinations. Material and Methods:Patients with AGC in cervicovaginal cytology were included in this study between March 2011 and March 2018 and patient data were collected retrospectively among all cytology results. AGC classification of cervicovaginal cytology were based on the Bethesda 2001 classification system. Results:The total prevalence of cervical epithelial cell abnormality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…AIS lesions are precursors to invasive adenocarcithat tend to be deep and highly localized in the cervical crypt, making these lesions difficult to recognize. 27 They are also not easy to recognize by colposcopy. The advantage of the Pap test is that in cases with uncertain lesions the cells in a lesion can be extensively sampled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AIS lesions are precursors to invasive adenocarcithat tend to be deep and highly localized in the cervical crypt, making these lesions difficult to recognize. 27 They are also not easy to recognize by colposcopy. The advantage of the Pap test is that in cases with uncertain lesions the cells in a lesion can be extensively sampled.…”
Section: Discussionmentioning
confidence: 99%
“…AIS lesions are precursors to invasive adenocarcinoma that tend to be deep and highly localized in the cervical crypt, making these lesions difficult to recognize 27 . They are also not easy to recognize by colposcopy.…”
Section: Discussionmentioning
confidence: 99%
“…The solvent slides were prepared by liquid-based cytology. Disease-level cytological classifications were performed according to the Bethesda 2001 criteria (TBS2001) 15 H), internal epithelial lesion of low-grade scoliosis (L-SIL), and high-grade scoliosis internal epithelial damage (H-SIL). Cells isolated for HPV DNA extraction are stored in the vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the incidence of premalignant and malignant lesions in the endometrium and cervix was 27.6%. It was reported as 19%‐59% in patients with AGC‐NOS cytology results in previous studies 9,18‐20 …”
Section: Discussionmentioning
confidence: 88%
“…Of these, 4.3% was endometrial cancer and 2.4% was cervical cancer. Similarly, Yüksel et al 18 concluded that malignancy was 6.6% in patients with AGC‐NOS. In other studies, the frequency of endometrial cancer was reported between 2%‐4.8%, while cervical cancer frequency was 2.5%‐6% 2,23 …”
Section: Discussionmentioning
confidence: 93%